The golden age of pantomime : slapstick, spectacle and subversion in Victorian England - Richards, Jeffrey (Drama & performance studies (London, England), 2020)
Of all the theatrical genres most prized by the Victorians, pantomime is the only one to have survived continuously into the twenty-first century. It remains as true today as it was in the 1830s, that a visit to the pantomime constitutes the first theatrical experience of most children and now, as then, a successful pantomime season is the key to the financial health of most theatres. Many Victorian luminaries were devotees of the pantomime, notably among them John Ruskin, Charles Dickens, Lewis Carroll and W.E. Gladstone. In this vivid and evocative account of the Victorian pantomime, Jeffrey Richards examines the potent combination of slapstick, spectacle and subversion that ensured the enduring popularity of the form.